Chiral substrate-induced chiral covalent organic framework membranes for enantioselective separation of macromolecular drug - Xiaoyue Gao; Teng Ben (Nature Communications)
Abstract Chiral drugs are essential in modern medicine, but separating their enantiomers is challenging due to their similar physicochemical properties. However, traditional methods are often costly and inefficient. Here we show that chiral covalent organic framework (CCOF-300) membranes, induced by chiral dopants (L-( + )-/D-(–)-tartaric acid), can achieve high enantioselectivity in separating chiral drugs. Specifically, CCOF-300 membrane achieved 100% enantiomeric excess in separating racemic N-Fmoc-N’-[1-(4,4-Dimethyl–2,6-dioxocyclohexylidene)ethyl]-lysine (Fmoc-Lys(Dde)-OH). We found that size matching and differences in diffusion rates between enantiomers are key factors in chiral separation. Additionally, there were no significant differences in the binding energy between ibuprofen (IBU), Fmoc-Lys(Dde)-OH, and CCOF-300, indicating that binding energy is not the dominant factor in chiral separation. This study proposes a cost-effective and scalable method for chiral drug separation, highlighting the potential of chiral induction strategy in improving chiral separation technology in the pharmaceutical industry.